Peran Pekerja Sosial Dalam Meningkatkan Kecerdasan Emosional Anak Asuh di Panti Asuhan Penuh Pengharapan - Sani Susanti; Khodijah Tussolihin Dalimunthe; Geovani A K br Sitepu; Ela Saputri; Fitri Salsabila (JURNAL ILMIAH NUSANTARA, 2024)
Emotional intelligence is an important key in helping foster children manage their emotions healthily and face life's challenges better. This research aims to analyze the role of social workers in increasing emotional intelligence, especially in terms of increasing the emotional intelligence of foster children, at the Full Hope Orphanage. Data was collected through direct observation and interviews with orphanage managers. The research results show that guidance and emotional support actually have a positive impact in improving the ability of foster children in orphanages to better manage their emotions. Improved emotional intelligence helps foster children face the challenges of daily life more resiliently, as well as improving the quality of their interpersonal relationships. From the research results, it can be concluded that the role of social workers in increasing the emotional intelligence of foster children in orphanages is very significant, social workers can be agents of change who encourage the emotional growth of foster children and help them reach their full potential.